2017
DOI: 10.21767/2386-5180.1000183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacteriological Quality of Surface, Well, Borehole and River Water in Khana Local Government Area of Rivers State, Niger Delta

Abstract: In most rural communities, water is consumed without testing its potability and the major sources of water apart from rainfall are surface and river water; in some cases, borehole water. Water samples from surface, river, well and borehole water in different Communities in Khana Local government area was randomly collected and bacteriological analysis was carried out on them. The results showed that the least microbial load was from that of borehole water which had an average microbial load of 1.78 × 10 3 whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The number of E. coli organisms in all sampling stations was extremely above the permissible limit. Studies have reported a high count of coliforms in surface water [39][40][41]. The presence of E. coli in all the water samples is evidence of faecal contamination from human and warm-blooded animals which may indicate the presence of pathogenic organisms.…”
Section: Discussionmentioning
confidence: 97%
“…The number of E. coli organisms in all sampling stations was extremely above the permissible limit. Studies have reported a high count of coliforms in surface water [39][40][41]. The presence of E. coli in all the water samples is evidence of faecal contamination from human and warm-blooded animals which may indicate the presence of pathogenic organisms.…”
Section: Discussionmentioning
confidence: 97%
“…In general, the absence of faecal coliforms in borehole water means that it was accurately dug to get clean water. This borehole perhaps might not be located close to a toilet or suck away system; had consistent washing and disinfection of the water tank, and might also had a water purifier which increased water quality (Okoro et al, 2017;Obioma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They can also cause bacteremia when introduced into the bloodstreams. In addition, some strains of E. coli were capable of producing enterotoxins in the human small intestine which can also cause diarrhoea (Obioma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…protozoa and helminths) are the most common and widespread health risk associated with drinking-water [6]. Consumption of untreated water has been reported to cause different types of water borne diseases including cholera, typhoid, hepatitis A and diphtheria [7] For instance, cholera outbreak has been reported in Zimbabwe, India and Nigeria which was caused by the presence of Vibrio cholerae (gram negative bacterium) in municipal taps and wells [8], 80% of sicknesses and deaths among children worldwide have been associated with the consumption of unsafe water [9]. Most gramnegative bacteria are involved in food and water borne diseases.…”
Section: Introductionmentioning
confidence: 99%